THE INFLUENCE OF IMAGE AND CUSTOMERS’ SATISFACTION TOWARDS CONSUMERS’ LOYALTY TO TRADITIONAL FOODS IN SURABAYA - Christina Esti Susanti (Jurnal Manajemen Pemasaran, 2009)
This research is aimed to give contribution of thought to the influence of image and customer’s satisfaction towards the customers’ loyalty to traditional foods in Surabaya. This research uses exploratory research method to determine the population and sample. The populations of this research are consumers aged ≥ 17 years old, living in Surabaya, and having consumed traditional foods. The samples are taken by using simple random sampling. Questionnaires are used as instruments to get the primary data in order to identify the fact or real condition in the field. The results of the research show that (1) image and consumers’ satisfaction strongly, positively, and significantly influence the consumers’ loyalty both partially and simultaneously, and (2) consumers’ satisfaction dominantly influence the consumers’ loyalty towards traditional foods in Surabaya. Based on the results of the research, it is suggested that the traditional food’s sellers or agents in Surabaya should pay attention, maintain, and improve the image of the products and consumers’ satisfaction. If there is any alternative of selling strategy to choose, the most important thing to be considered is the consumer satisfaction strategy. It is because variable of satisfaction dominantly affects the consumers’ loyalty toward the traditional foods in Surabaya.